Hypoalbuminemia Leads to An Increased Risk Of Mortality And Re-Operation Within 3-Months In Patients 75< Years Of Age After Surgery For Hip Fractures - KURTOGLU, Alper; OZTAS SUKUR, Nur Ece; Şükür, Erhan; Kochai, Alauddin; KESKIN, Dogan; OZ, Ihsan; Sen, Zafer (Progress in Nutrition, 2022)
Background: The focus of this study is to ascertain a baseline nutritional level of adults 75 years old who are hospitalized for hip fracture surgery, and to assess the effects on the mortality rates and post-operative complications that require re-operation within 3 months of the initial surgery. Material and Methods: A total of 240 patients having surgery for fractured hips during 2017-2019 were identified. Patients' characteristics, including pre-operative laboratory findings, complications and reoperation rates were assessed. Multivariate logistic regression analysis was used to establish the effect of hypoalbuminemia and total lymphocyte count on the rates of 3-month post-operative complications, re-operation and mortality. Results: Among patients studied, 153 had hypoalbuminemia (albumin levels